Penerapan Model Promblem Based Learning untuk Meningkatkan Kemampuan Komunikasi Matematis Peserta Didik - Masniawita Gloria Sinaga; Hidayat Hidayat; Dwi Novita Sari; Atika Erlina Nasution; Novita Syahputri (Journal on Education, 2024)
This study employs the Problem Based Learning (PBL) approach to better equip XI-IPS 3 students at SMA Negeri 2 Medan to communicate mathematical ideas and concepts. In this complicated information age, mathematical communication abilities are essential, yet reality shows that this ability is still low among Indonesian students. Each of the two cycles of this classroom action study included steps of planning, carrying out the action, observing the results, and reflecting on the experience. Data were collected through written tests and observations to assess students' mathematical communication skills and teachers' proficiency in applying PBL. The results show a significant improvement in students' mathematical communication abilities. Before the intervention, only 28.57% of students reached the Minimum Completion Criteria (KKM), but after two PBL cycles, this percentage increased to 77.14%, exceeding the 75% target. Improvements were also seen across all mathematical communication indicators, including representing problems, explaining strategies, and interpreting solutions. This research proves that PBL is effective in enhancing students' mathematical communication skills.